Psycho-Social Factors as Predictors of Female Academic Staff Job Commitment in Unversities in South Western Nigeria (2013)
Most female academics have over the years developed low contentment and feelings about various aspects of their jobs arising from work-family life stress. This has resulted in a weak attachment to their institutions and low level of willingness to exert high level of efforts on their jobs. Though literature on job commitment and performance in Nigerian universities is vast and rich, most past studies have focused more on the male faculties’ job commitment with little attention paid to the females’. This study, therefore, investigated psycho-social factors predisposing job commitment of female academic staff in universities in South Western Nigeria. The survey research design was adopted. The total enumeration and purposive sampling techniques were used to select 1125 single and married female academics (922 junior and 203 senior academic staff) from nine universities comprising: three each of federal, state and private. Six instruments were used: Social Factors Scale (r=0.62), Self- Efficacy Scale (r=0.75), Self- Esteem Scale (r=0.83), Self- Concept Scale (r=0.85), Work Value Scale (r=0.71) and Female Academics’ Job Commitment Scale (r=0.64). These were complemented with eighteen sessions of in-depth interviews (IDIs) with two female academics per university. One research question was answered and five hypotheses were tested at 0.05 level of significance. Data were analysed using descriptive statistics, t- test, Pearson Product Moment Correlation, multiple regression and content analysis. Psycho-social factors significantly correlated with female academics’ job commitment (F (7, 1118) =90.14; R2=.571, p<0.05). They jointly accounted for 32.2% of the variance in job commitment; with social factors accounting for 10.0 % and psychological factors accounting for the remaining 22.2%. Their relative contributions were: psychological factors (β=.467, p<0.05) and social factors (β=.210, p<0.05). Significant relationship existed between each of the components of the psychological factors and female academics’ job commitment as ranked: self esteem (r=.577), self concept (r=.517), work values (r=.468) and self efficacy (r=.344). Further, significant relationship also existed between each of the components of social factors and job commitment as follows: networking (r=.521), mentoring (r=.348), educational attainment (r=.089), work experience (r=.029), age (r=.019) and marital status (r= -.038). There was a significant difference in female academics’ job commitment on the basis of rank (t=6.26, p<0.05): junior academic staff (=46.89) and senior academic staff (=49.55). Also, significant difference was observed in female academics’ job commitment based on institutional ownership: federal (=48.42), state (=48.14) and privately owned (=45.91). This, therefore, show that female academics’ job commitment was more pronounced in federal universities followed by state and private universities respectively. The IDI revealed that the university’s academic culture was too rigid and insensitive to the females’ work-family life stresses particularly among the junior levels. Psycho-social factors contributed fairly to female academics’ job commitment. Therefore, there is the need to provide female academics with necessary career information and supports through networking /mentoring within a more women-friendly academic environment.